2019
DOI: 10.3390/jcm8081114
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Risk Factor Control After Myocardial Infarction—A Need for Better Prevention Programmes

Abstract: Introduction: Long-term prognosis of myocardial infarction (MI) is still serious, especially in patients with MI and cardiogenic shock. To improve long-term prognosis and prevent recurrent events, sustainable cardiovascular risk factor control (RFC) after MI is crucial. Methods: The article gives an overview on health care data regarding RFC after MI and presents recent trials on modern preventive strategies that support patients to achieve risk factor targets during long-term course. Results: International re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…However, the intensive prevention programme IPP-Y was associated with a significant improvement of risk factor control in young MI patients. The effects of the programme were similar compared to a cohort of older patients (≤75 years) that our study group had investigated in a previous trial, 7,8 or to results that have been reported by other prevention programmes in older patients. 9 Although it might be assumed that young patients focus on business and families and do not find time for preventive activities, our data show that prevention programmes can be effective even in young MI patients.…”
Section: Discussionsupporting
confidence: 68%
“…However, the intensive prevention programme IPP-Y was associated with a significant improvement of risk factor control in young MI patients. The effects of the programme were similar compared to a cohort of older patients (≤75 years) that our study group had investigated in a previous trial, 7,8 or to results that have been reported by other prevention programmes in older patients. 9 Although it might be assumed that young patients focus on business and families and do not find time for preventive activities, our data show that prevention programmes can be effective even in young MI patients.…”
Section: Discussionsupporting
confidence: 68%
“…Finally, modernisation of prevention programmes, for example by a more continuous telemetric risk factor control, may be promising. 8 * As the response rate in the intervention group was lower than the expected 70%, we did not reach the required sample size after we invited 587 intervention patients. Therefore we had to invite 226 extra patients in the intervention group (totally invited n = 813) and matched them retrospectively to the usual care group.…”
Section: Implications For Research and Practicementioning
confidence: 93%
“…7 So far, studies on the effectiveness of CVRM programmes are scarce and the available evidence is inconsistent. [8][9][10] Some studies showed a trend towards improved lifestyle, but did not show an effect on cardiovascular risk factors and cardiovascular outcomes. [11][12][13] However, the studies were heterogeneous in design, target population and interventions tested and adequate comparison with usual care was often lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The ARIC study was aimed originally at assessing the risk factors of atherosclerosis and its clinical outcomes, namely the trends in rates of coronary heart disease and hospitalized MI among men and women aged 45–64 (González et al., 2018; Investigators, 1989). In clinical practice, detecting risk factors of MI is crucial for disease prevention and selecting treatment that is more cost‐effective (Osteresch et al., 2019). Therefore, our goal here is to investigate the effects of potential clinical and demographic features on the MI risk with the outcome as the time to hospitalization of acute MI since enrollment.…”
Section: Data Applicationmentioning
confidence: 99%